Consider this is taking place in the hyperbolic half plane model

If $x_1 \not= x_2$ then the line $\overleftrightarrow{AB}$ has the following equation $(x-a)^2+y^2=r^2$. Prove that $r=\sqrt{(x_1-a)^2+y_1^2}=\sqrt{(x_2-a)^2+y_2^2}$ and $$a=\frac{x_2^2+y_2^2-x_1^2-y_1^2}{2(x_2-x_1)}$$

Now I understand that $r$ comes from taking the square root of the equation and recognizing the radius is the same from both points. Now I'm not quite sure how to arrive at $a$ which seems to be the center of the half circle.


You have:


Squaring both the sides we get:

$$(x_1-a)^2+y_1^2=(x_2-a)^2+y_2^2$$ $$(x_1-a)^2-(x_2-a)^2=y_2^2-y_1^2$$ $$(x_1-a-x_2+a)(x_1-a+x_2-a)=y_2^2-y_1^2$$ $$(x_1-x_2)(x_1+x_2-2a)=y_2^2-y_1^2$$ $$x_1^2-x_2^2-2a(x_1-x_2)=y_2^2-y_1^2$$ $$2a(x_2-x_1)=x_2^2+y_2^2-x_1^2-y_1^2$$ $$a={x_2^2+y_2^2-x_1^2-y_1^2\over2(x_2-x_1)}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.